Metal halide perovskites for solar‐to‐chemical energy conversion in aqueous media - Chunhua Wang; Yang Ding; Yannan Wang; Zhirun Xie; Zhiyuan Zeng; Xin Li; Yun Hau Ng (Carbon Energy)
Abstract Solar‐driven energy conversion is a promising technology for a sustainable energy future and environmental remediation, and an efficient catalyst is a key factor. Recently, metal halide perovskites (MHPs) have emerged as promising photocatalysts due to their exceptional photoelectronic properties and low‐cost solution processing, enabling successful applications in H2 evolution, CO2 reduction, organic synthesis, and pollutant degradation. Despite these successes, the practical applications of MHPs are limited by their water instability. In this review, the recently developed strategies driving MHP‐catalyzed reactions in aqueous media are outlined. We first articulate the structures and properties of MHPs, followed by elaborating on the origin of instability in MHPs. Then, we highlight the advances in solar‐driven MHP‐based catalytic systems in aqueous solutions, focusing on developing external protection strategies and intrinsically water‐stable MHP materials. With each approach offering peculiar sets of advantages and challenges, we conclude by outlining potentially promising opportunities and directions for MHP‐based photocatalysis research in aqueous conditions moving forward. We anticipate that this timely review will provide some inspiration for the design of MHP‐based photocatalysts, manifestly stimulating their applications in aqueous environments for solar‐to‐chemical energy conversion.